2010
DOI: 10.1007/s11224-010-9632-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structural characterization of novel 2-benzimidazolylthioureas: adducts of natural isothiocyanates and 2-amino-1-methylbenzimidazole

Abstract: Adducts of natural allyl, phenethyl, and benzyl isothiocyanates and 2-amino-1-methylbenzimidazole were synthesized. After optimization of the reaction conditions, the target 2-benzimidazolylthioureas were obtained in reasonable yields. The detailed molecular and crystal structures of these compounds were characterized by spectroscopic and X-ray methods. Spectral analysis demonstrated that N-(1-methylbenzimidazolyl)-N 0 -allylthiourea, N-(1-methylbenzimidazolyl)-N 0 -benzylthiourea, and N-(1-methylbenzimidazoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…The structure of compounds 3a–o and 4a–h , j–o was proved by NMR spectroscopy, mass spectrometry, and elemental analysis. In the 1 H NMR spectra of compounds 3 and 4 , we observed a single set of signals, which is typical for one of the possible isomeric forms of these compounds: endo - 3 , 4 and exo - 3 , 4 (Scheme ), which depends on the medium . It was previously shown that the structurally similar benzimidazole derivatives exist in solution as a single tautomeric form containing an exocyclic double CN bond. , For the studied compounds 3a–f , j–l and 4a–f , j–l (R 1 = R 2 = R 3 = H), the signals for NH proton were observed as a singlet with an integral intensity of 2 in the region of 12.23–12.93 ppm for amides and 13.43–13.73 ppm for thioamides, respectively, which indicates a similar proton environment in both NH groups and is consistent with the previously published structurally similar substances. , For compounds 3g , i , m , n and 4g , m , n containing a substituent in the benzimidazole nucleus (R 1 = Me, CF 3 , CO 2 Et, R 3 = H), the NH proton signals are observed as a broadened singlet or as two singlets.…”
Section: Resultsmentioning
confidence: 72%
“…The structure of compounds 3a–o and 4a–h , j–o was proved by NMR spectroscopy, mass spectrometry, and elemental analysis. In the 1 H NMR spectra of compounds 3 and 4 , we observed a single set of signals, which is typical for one of the possible isomeric forms of these compounds: endo - 3 , 4 and exo - 3 , 4 (Scheme ), which depends on the medium . It was previously shown that the structurally similar benzimidazole derivatives exist in solution as a single tautomeric form containing an exocyclic double CN bond. , For the studied compounds 3a–f , j–l and 4a–f , j–l (R 1 = R 2 = R 3 = H), the signals for NH proton were observed as a singlet with an integral intensity of 2 in the region of 12.23–12.93 ppm for amides and 13.43–13.73 ppm for thioamides, respectively, which indicates a similar proton environment in both NH groups and is consistent with the previously published structurally similar substances. , For compounds 3g , i , m , n and 4g , m , n containing a substituent in the benzimidazole nucleus (R 1 = Me, CF 3 , CO 2 Et, R 3 = H), the NH proton signals are observed as a broadened singlet or as two singlets.…”
Section: Resultsmentioning
confidence: 72%
“…This phenomenon was also observed in the characterization of novel 2-benzimidazolylthioureas by Śmiechowska and co-workers. 32 The occurrence of tautomer B can also be seen with benzimidazole carbamates, a group that is contained in many medically relevant compounds. [33][34][35][36] Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the work by Ś miechowska et al [234] an optimized procedure for conversion of natural isothiocyanates to N-(1-methylbenzimidazolyl)-N 0 -allylthiourea, N-(1-methylbenzimidazolyl)-N 0 -benzylthiourea and N-(1-methylbenzimidazolyl)-N 00 -phenethylthiourea is presented. The obtained products were characterized spectroscopically and their X-ray single crystal structures were determined.…”
Section: Issuementioning
confidence: 99%